Goblet Cell Carcinoids of the Appendix - Nanna Holt; Henning Grønbæk (The Scientific World Journal)
Goblet cell carcinoid (GCC) tumors are a rare subgroup of neuroendocrine tumors almost exclusively originating in the appendix. The tumor most often presents in the fifth or sixth decade with a clinical picture of appendicitis or in advanced cases an abdominal mass associated with abdominal pain. Histologically tumors are most often positive for chromogranin A and synaptophysin, however, less homogenous than for classic appendix carcinoids. The malignant potential is higher than that for the classic appendix carcinoids due to local spread and distant metastases at diagnosis and the proliferation markers (Ki67 index) may determine prognosis. Octreotide receptor scintigraphy is usually negative while CT/MRI scans may be useful. Chromogranin A is usually negative and other biomarkers related to the mucinous component or the tumor (CEA, CA-19-9, and CA-125) may be used. Surgery is the main treatment with appendectomy and right hemicolectomy while patients with disseminated disease should be treated with chemotherapy. Overall 5-year survival is approximately 75%. The diagnosis and treatment of GCC tumorss should be restricted to high volume NET centers in order to accumulate knowledge and improve survival in GCC NET patients. The aim of this paper is to update on epidemiology, clinical presentation, and diagnostic markers including Ki67 index, treatment, and survival.